Sociological Analysis of the Situation and Prospects of the Development of Socially Responsible Business in Kazakhstan - Alpeissova, Sholpan (Волинський національний університет імені Лесі Українки, 2021)
The aim of the article is to analyze promising areas of socially respon-sible business development in Kazakhstan. The term «socially responsible business» the author understands a wide range of actions of private capital in the development of specific areas (regions, communities, conglomerates), where the company is located, care for the environment at its place of operation, contribution to the economy as a whole and social capital employee, in particular. The article considers socially responsible business as one of the key markers of sustainable development of regions and the state. Based on a sociological analysis of key aspects of modern development of socially responsible business, the author concludes that strengthening the social responsibility of business, encouraging social activity of entrepreneurs are necessary conditions for sustainable development of society. In addition to the positive trends on the way to the formation of corporate social responsibility, there are many unresolved issues current issues and problems that need to be solved and studied by scientists.
Keywords: responsibility; socially responsible business; standard; criteria; social responsibility strategy; concept of socially responsible business; 316.336.021